Green and efficient synthesis of an adsorbent fiber by preirradiation‐induced grafting of PDMAEMA and its Au(III) adsorption and reduction performance. Issue 25 (3rd March 2017) - Liu, Xiyan; Ao, Junxuan; Yang, Xiaojuan; Ling, Changjian; Zhang, Bowu; Wang, Ziqiang; Yu, Ming; Shen, Rongfang; Ma, Hongjuan; Li, Jingye
ABSTRACT: N, N ‐Dimethylamino ethyl methacrylate (DMAEMA) is covalently bonded on a commercial polyethylene‐coated polypropylene skin‐core structure fiber (PE/PP) in aqueous and MeOH/H2 O solutions by a one‐step green reaction using radiation‐induced graft polymerization. The effects of the absorbed dose and solvent system on grafting yield are investigated, while the chemical and physical properties of the functionalized fiber are also evaluated. The fiber with a Dg of 51.6% exhibited good adsorption capacity of Au(III) ions over a large range of concentrations (from 10 to 2.5 g L −1 ) in both batch and flow‐through adsorption tests. The highest capacity of Au was 949.3 mg g −1 . After elution, the adsorbents can be reused without any further regeneration for at least five adsorption‐desorption cycles. Additionally, the fibers show high selectivity for Au(III). The distribution coefficient of Au(III) is 10 4 to 10 5 times higher than that for Cu(II), Fe(III), Ni(II), and Pb(II) even at 100 times lower Au(III) concentration compared to the co‐existing metal ion concentration. This study provides an effective and novel approach for gold recovery from aqueous solutions. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44955. Abstract :